Cultural-ethnic landscape of terrace housing community in peninsular Malaysia - Said, Ismail (Penerbit UTM Press, 2001)
Cultural-ethnic landscape symbolizes the belief and cultural values of an ethnic group living in a community. The landscape is an expression of people's idea and work; illustrating intrinsic understanding and relationship of people to their fellow beings and environment. Such landscape is significant to the human community development and more challenging to establish it in a multi-ethnic society such as terrace house neighborhood in Peninsular Malaysia than in homogenous society. This research investigates the characteristics of terrace house gardens from three ethnic groups, namely, Malays, Chinese and Indians. Through inventory and analysis of 23 neighborhoods in Peninsular Malaysia, it is found that 52% of the terrace houses have gardens. The design of garden and its features are partially influenced by ethnicity belief of the resident. The differences are in selection of plant species which are determined by the religious belief and ritual rite of the ethnic group. In hierarchical importance, the plant species are planted in the house garden for five reasons or uses, namely, (i) decoration, (ii) food, (iii) medicine and cosmetic, (iv) ritual, and (v) provision of shade.